Global warming and testis function: A challenging crosstalk in an equally challenging environmental scenario - De Toni, Luca; Finocchi, Federica; Jawich, Kenda; Ferlin, Alberto (Frontiers in Cell and Developmental Biology, 2023)
Environmental pollution, accounting for both chemical and physical factors, is a major matter of concerns for its health consequences in both bumans and animals. The release of greenhouse gases with the consequent increase of environmental temperatures is acknowledged to have a major impact on the health state of both animals and humans, in current and future generations. A large amount of evidence report detrimental effectcs of acute heat stress on testis function, and particularly on the spermatogenetic and steroidogenetic process, in both animal and human models, which is largely related on the testes placement within the scrotal sac and outside the abdomen, warranting an overall scrotal temperature of 2-4 °C lower than core body temperature. In this review the a thorough evaluation of the effect of the environmental temperature on testicular function will be provided. In particular, basic concepts of body thermoregulation will be discussed together with available data about the association between testis damage and heat stress exposure. In addition, the possible association between global warming and the secular decline of testis function will be critically evaluated in the light of the available epidemiological studies.